Tradition of Dreadlocks Shaving Ritual (Gimbal) in Dieng Plateau Wonosobo - Nor Holis (Metaphor, 2019)
Ritual cukur rambut gimbal or dreadlocks shaving ritual is tradition ritual which is done by people who live in Dieng plateau. The ritual is inherited from ancestor of the Dieng people, Kiai Kolodete. This ritual aims to eliminate the dreads in children which done based on Javanese calendar calculation. This paper aims to find out the relationship between the ritual and myth and Dieng people’s belief. Finding out the good and correct ritual procession based on empirical facts of the local community is the goal of this research as well. Parikesit is the village which is located in Kejajar sub-district, Wonosobo in Dieng plateau. There are some children with the dreadlocks who live in the village. Therefore, its people still maintain the ritual well. Parikesit is chosen to collect the information about the ritual of this research by interviewing its people. Meanwhile, this research also uses some books to define the myth and the ritual. Dreadlocks shaving ritual is done as a form of praying to dreads in children do not grow anymore. This ritual is done differently in every village in Dieng plateau. There are some communities with Javanese belief (Kejawen) held the ritual in Arjuna temple area with Javanese tradition and the ritual also held by other communities at their own home like other traditional party based on their religion (slametan). This ritual basically has same essence which is to pray and fulfill the desires of the children (who will be shaved) which is an absolute requirement.